Operating and Service Instructions, Beckman Astra Automated Stat/Routine Analyzer Systems - Underwood, Tom (1983)
Pages left intentionally blank have been omitted. The Astra line of analyzers used multiple channels to perform continuous flow and discrete analyses of electrolytes and "routine chemistries."
Keywords: Electrochemical analysis; Scientific apparatus and instruments; Beckman Instruments, Inc.